Influence of Adhesive Tapes as Thermal Interface Materials on the Thermal Load of a Compact Electrical Machine - Henrik-Christian Graichen; Jörg Sauerhering; Olena Stamann; Frank Beyrau; Gunar Boye (World Electric Vehicle Journal, 2022)
In this article, a novel form of thermal interface material (TIM), represented by three industrially manufactured pressure-sensitive adhesive (PSA) tapes with electrical insulating properties, is characterized regarding its applicability in an electric motor with air-gap winding. Firstly, the adhesion performances, in terms of the winding process, were investigated experimentally. Here, every TIM shows sufficient shear strength for the wire–TIM joints, as well as peel adhesion to the laminated iron core. Secondly, the thermal–physical properties of the TIMs are inspected experimentally via laser flash analysis (LFA) and differential scanning calorimetry (DSC). For every TIM, the value of the thermal resistance can double if the relatively smooth surface (Ra = 0.2 μm) of the adjacent layers is interchanged with a rougher one (Ra = 2.0–3.7 μm). Additionally, the TIM’s performance at the system level is examined. Therefore, a flat test section, according to the specifications of the original motor, is studied experimentally and numerically utilizing infrared (IR) thermography and the finite element method (FEM). The focus is set on the heat flow and temperature distribution in the test section under varying thermal loads, mass flow, and variety of TIMs.